PENGARUH GAYA HIDUP (LIFESTYLE) DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus pada Pelanggan Peacockoffie Semarang) - Suci Dwi Pangestu; Sri Suryoko (Jurnal Ilmu Administrasi Bisnis, 2016)
The rapid growth of coffee shops within a few years makes the competition tighter. Consumer behavior in decision-making is influenced by several factors such as lifestyle and price. Peacockoffie is one coffee shop that is known in Semarang city. The problem in this research is the price increases that is carried out by Peacockoffie in 2014 resulting in a decrease amount of daily transactions amid growing coffee shop in the city of Semarang. The result shows that the lifestyle and the price have positive and significant impacts upon decision of purchasing. It can be seen from the outcome of simple linier regression of lifestyle towards decision of purchasing and t test. From those two variables (lifestyle and price) that had been partially and simultaneously analyzed, the coefficient of price is higher than lifestyle coefficient. In details, price has the biggest impact towards the decision of purchasing the products of Peacockoffie Semarang, reaching the number 0,288, compared with lifestyle that only get 0,057. The coefficient of determination (R2) of lifestyle and price is 19,6%. This means 19,6% of purchasing decision can be explained by those two variables, while the other 80,4% can be explained by another variable. The suggestions that can be given to increase the purchasing decision is that Peacockoffie should establishes standard operating procedure (SOP) in service and product presentation.